The analytic Philosophy de Umberto Scarpelli. From the analysis of the evaluative language to the principles of bioethics - Zorzetto, Silvia (2014)
It is a biographical article about Uberto Scarpelli and its main aim is to give a philosophical scheme of Scarpelli, commenting the most important aspects of his life, his main works and the itinerary of his thought. The article depicts as a transversal idea that for Scarpelli there is no side study between philosophy and the General Theory of Law; quite the contrary, both of them are always in complete joining and mutual feedback. That is the reason why the article shows a scarpellian sight of language analysis, epistemology, ethical deliberation and General Theory of Law.